GAMBARAN DEPRESI MAHASISWA PROGRAM STUDI KESEHATAN MASYARAKAT PSDKU UNIVERSITAS AIRLANGGA DI BANYUWANGI: Description of Depression Among Student in Public Health Major Universitas Airlangga Banyuwangi - Hayunda Fajri Sholikhah; Rochmad Ardiansyah Pratama; Gayatri Ayodhya; Erni Astutik (Journal of Community Mental Health and Public Policy, 2019)
ABSTRACT Prevalence of depression remains high worldwide and leads to high mortality and suicidal rate. In Indonesia, depression is still a serious problem and its prevalence is increasing every year. The incidence of depression in students varies by university. This study aims to describe the dep ression rate in students of Public Health Study Program at Universitas Airlangga Banyuwangi. This study uses a cross-sectional study design with descriptive studies. The respondents was 68 students of Public Health Study Program of Universitas Airlangga Banyuwangi, aged 17-21 years. Data is analyzed univariably. The results showed that of 68 respondents there were 57.4% of respondents who were depressed. Of the number of respondents who were depressed, 59% were in the young age category and 87.2% were female. Whereas if viewed based on the semester taken by respondents at the time of the study, the majority of respondents were in semester 2 that is equal to 41%, and most respondents had a GPA not cumlaude with a number of 59%. The conclusion of this study is depression prevalence rate of students of the Banyuwangi Public Health Study Program is higher than those who are not depressed. Better diagnosis and treatment of depressed students can help reduce suicide rates in adolescents